Impact of mobile phone based agro-advisories on knowledge of sunflower (Helianthus annuus L.) farmers’: IMPACT OF MOBILE PHONE BASED AGRO-ADVISORIES ON SUNFLOWER FARMERS’ - G D S KUMAR; M PADMAIAH; K ALIVELU; P MADHURI (Journal of Oilseeds Research, 2013)
The productivity of rabi sunflower (Helianthus annuus L.) is low in Andhra Pradesh (892 kg/ha). In order to achieve higher productivity of sunflower, farmers need to access a wide range of information related to production technologies, post-harvest processes, remunerative markets, credit and weather. The increasing penetration of mobile phone networks and handsetsin India presents an opportunity to make useful information more widely available and plays a significant role in technology transfer. Thisstudy was conducted with sunflower farmers of Mahaboobnagar district, Andhra Pradesh, India with the objectives of assessing the farmers preferred extension delivery methods, their needs and perceptions of use of mobile phones and the gain in knowledge on sunflower production technologies due to mobile phones. The knowledge scores showed significant differences between pre- and postdissemination of messages over mobile phones, which indicated that substantial improvement in knowledge, is possible with the use of mobile phones as source of knowledge access.